2017
DOI: 10.1007/s10900-017-0320-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Prevention of Hypertension in Filipino Americans

Abstract: Background Despite that Filipino Americans represent an important target group for hypertension, health behaviors associated with hypertension in this population have not been well studied. Methods Two hundred Filipino Americans from eight community-based organizations completed the study. Information was collected to determine whether modifiable behavioral factors, as well as acculturation and demographic characteristics, were associated with hypertension status in Filipino Americans. Results Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Prevalence of HBP was also highest among Filipina (30.6%), intermediate among Japanese (27.9%) and lowest (18.2%) among Chinese American control women. High prevalence of hypertension and other components of metabolic syndrome has been reported in other studies of Filipino in the US . In a meta‐analysis of 30 studies on hypertension and breast cancer, a significant positive association was found in postmenopausal women (RR 1.20, 95% CI 1.09–1.31) but not in premenopausal women (RR 0.97, 95% CI 0.84–1.12) and was more consistent in studies conducted in western than in Asian populations .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Prevalence of HBP was also highest among Filipina (30.6%), intermediate among Japanese (27.9%) and lowest (18.2%) among Chinese American control women. High prevalence of hypertension and other components of metabolic syndrome has been reported in other studies of Filipino in the US . In a meta‐analysis of 30 studies on hypertension and breast cancer, a significant positive association was found in postmenopausal women (RR 1.20, 95% CI 1.09–1.31) but not in premenopausal women (RR 0.97, 95% CI 0.84–1.12) and was more consistent in studies conducted in western than in Asian populations .…”
Section: Discussionsupporting
confidence: 71%
“…High prevalence of hypertension and other components of metabolic syndrome has been reported in other studies of Filipino in the US. 21,23,39 In a meta-analysis of 30 studies on hypertension and breast cancer, a significant positive association was found in postmenopausal women (RR 1.20, 95% CI 1.09-1.31) but not in premenopausal women (RR 0.97, 95% CI 0.84-1.12) and was more consistent in studies conducted in western than in Asian populations. 40 Hypertension may increase risk of breast cancer by mediating effects via adipose tissues, inflammation or other pathways.…”
Section: Cancer Epidemiologymentioning
confidence: 80%
See 1 more Smart Citation
“…Disparities in hypertension among non-Hispanic blacks has been well-documented ( Mensah et al, 2005 ; Ong et al, 2007 ; Centers for Disease Control and Prevention, 2005 ; Barnes et al, 2008 ). Research within Asian American communities is limited, yet a growing body of evidence indicates that compared to non-Hispanic whites, Filipino Americans experience a higher burden of hypertension (23.9–67%) ( Barnes et al, 2008 ; Jose et al, 2013 ; Zhao et al, 2015 ; Bayog and Waters, 2017 ; Ma et al, 2017 ; Ye et al, 2009 ; Ursua et al, 2013 ; Ursua et al, 2014a ) and lower rates of control ( Zhao et al, 2015 ; Ursua et al, 2014a ; Ea et al, 2018 ). Given the rapid population expansion of Filipino Americans in the US (38.9% increase between 2000 and 2010) ( U.S. Census Bureau, 2012 ) as well as in regions such as New York City, ( Federation AA, 2009 ) strategies to mitigate the burden of hypertension among Filipinos are warranted ( Ursua et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…Culturally, Filipinos in the US tend to acculturate faster and have higher English proficiency than the Chinese ( Eng et al, 2008 ). Regarding health status, Filipino Americans have higher rates of hypertension, obesity and diabetes compared to other Asian ethnic groups and Non-Hispanic whites ( Ma et al, 2017 ; Wang et al, 2011 ; Ye et al, 2009 ). However, no study has examined the differences of health behaviors between Chinese and Filipino Americans among the individuals living with CMD.…”
Section: Introductionmentioning
confidence: 99%